VARIABILITAS HARGA SAHAM PADA PERIODE PERDAGANGAN DAN BUKAN PERDAGANGAN (Studi pada Saham-Saham yang Termasuk dalam Kelompok LQ45) - , Raras Ayu Puspitasari, SE. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Efficient capital market is defined as the market prices of securities has already reflect all relevant information. In other words, the information received by investors may affect the volatility of the stock. Movement (volatility) share price reflects two things: the influence of information arrival (arrival information) and noise (Huang et.al